The self-regulation in the environment of the listed companies: notes on the good corporate governance in Spain and Europe - López Jiménez, David (2012)
One of the scenarios in which the phenomenon of self-regulation is occupying a very important place is the corporate. Indeed,in the environment of the listed companies, due in large part to the scandals that occurred in that sector, there has beenapproved a list of good corporate government. Such practices have spread worldwide. In this paper, we will make certainconsiderations that focus on the community space, with special attention to the actual situation in Spain.